Iran’s Nuclear Policy: Russia’s Perspective - Thowhidul Islam (Central European Journal of International & Security Studies, 2011)
Despite Iran’s claim that its nuclear intentions are based strictly on developing the technology for peaceful purposes, the regime is constantly criticised – notably by the US and EU – and has come under immense pressure, resulting in debilitating international sanctions to prod the regime to be more transparent in its nuclear activities. Despite this, Russia continues to support Iran’s nuclear goals. This work sheds some light on how Russia views Iran’s nuclear ambitions and provides an in-depth exploration of how far Iran has moved to becoming the world’s next nuclear power.